2011
DOI: 10.1021/nn202799d
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence and Chemiluminescence Resonance Energy Transfer (CRET) Aptamer Sensors Using Catalytic Hemin/G-Quadruplexes

Abstract: The incorporation of hemin into the thrombin/G-quadruplex aptamer assembly or into the ATP/G-quadruplex nanostructure yields active DNAzymes that catalyze the generation of chemiluminescence. These catalytic processes enable the detection of thrombin and ATP with detection limits corresponding to 200 pM and 10 μM, respectively. The conjugation of the antithrombin or anti-ATP aptamers to CdSe/ZnS semiconductor quantum dots (QDs) allowed the detection of thrombin or ATP through the luminescence of the QDs that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(176 citation statements)
references
References 54 publications
(86 reference statements)
2
174
0
Order By: Relevance
“…Willner's group has exploited catalytic hemin/G-quadruplex DNAzymes for the detection of DNA, metal ions, aptamer-substrate complexes, thrombin, glucose oxidase, and ATP by using QD-CRET. [142][143][144][145] The hemin/G-quadruplex DNAzyme exhibits peroxidase-like activity that can catalyze the chemiluminescent reaction between luminol and H 2 O 2 . For DNA detection, three different colors of QDs (PL at 490, 560, and 620 nm) were functionalized with three different hairpin oligonucleotide probes that were complementary to three target oligonucleotide sequences of interest.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…Willner's group has exploited catalytic hemin/G-quadruplex DNAzymes for the detection of DNA, metal ions, aptamer-substrate complexes, thrombin, glucose oxidase, and ATP by using QD-CRET. [142][143][144][145] The hemin/G-quadruplex DNAzyme exhibits peroxidase-like activity that can catalyze the chemiluminescent reaction between luminol and H 2 O 2 . For DNA detection, three different colors of QDs (PL at 490, 560, and 620 nm) were functionalized with three different hairpin oligonucleotide probes that were complementary to three target oligonucleotide sequences of interest.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…Then, 250 μl of 20 mM H 2 O 2 stock solution was added quickly into the cuvette and emission spectra were recorded. Two samples were prepared; sample 1 was prepared in HEPES buffer 20 mM containing EDTA 0.1 mM, DMSO 1%, triton X-100 0.025%, KCl 150 mM, pH 8; in sample 2, KCl 150 mM was replaced with NaCl 150 mM pH [16][17][18][19].…”
Section: Measurement Of Dnazyme Activitymentioning
confidence: 99%
“…The design can also be modified for other oxidation reactions or biocatalytic processes that can directly or indirectly produce H 2 O 2 . Additional work done by Willner's group has shown that catalysis of the luminol-H 2 O 2 reaction by the HRP-mimicking hemin/G-quadruplex DNAzyme to produce CRET-sensitized QD emission is useful for the detection of aptamer substrates such as thrombin and ATP, as well as multiple DNA sequences (Freeman et al 2011b;Liu et al 2011). For the latter, the DNAzyme sequence was hidden within stem-loop oligonucleotides that opened in the presence of complementary target DNA to enable self-assembly of the hemin/Gquadruplex DNAzyme.…”
Section: Cret and Bret-based Bioanalysis With Quantum Dotsmentioning
confidence: 99%